“Paper, quills and drugs for ink”: office supplies in the diamonds administration in the 18th century - Quintão, Régis Clemente (Anais do Museu Paulista: História e Cultura Material, 2020)
This article discusses the import, circulation and use of office supplies by the Royal Diamond Extraction in Minas Gerais during the last decades of the 18th century, questioning about their importance for the administration and fiscal control intended by the authorities of that period. Utilizing sources belonging to the Real Erário fund from the Historical Archives of the Portuguese Court of Auditors, we unveiled the work of that institution and the consumption of account books, papers of varying quality and European manufacturers, quill pens and substances used in the production of iron gall ink. The study of those elements evinces not only their relevance to the bureaucratic activities of that society, but also a material dimension that we rarely see in the past. After all, such supplies and artifacts allow to understand some production conditions of documents preserved in archives and libraries.